Energy-saving low-rolling-resistance conveyor belt cover rubber and production method thereof
Patent Information
- Application Number
- CN202610603137.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-06
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-05-06
AI Technical Summary
针对现有技术的不足,本发明提供了一种节能低滚阻输送带盖胶及生产方法,解决现有输送带盖胶难以同时满足低滚动阻力、高拉伸强度、良好耐磨性和优异加工性能,导致长距离输送能耗高、使用寿命短的问题
(1)、该节能低滚阻输送带盖胶及生产方法,通过稀土顺丁中的C=C双键断裂和环氧天然橡胶中环氧基团-C(O)-交联在一起的协同效应,形成-C-C-O-C-稳定的三环环氧基团结构,在硫磺交联的作用下,部分形成共价键,形成更稳定的三维立体网状结构,键能高、弹性好、变形后内生热小,滞后损失较小。
Smart Images

Figure CN122145905B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of conveyor belt material technology, specifically to an energy-saving, low rolling resistance conveyor belt cover adhesive and its production method. Background Technology
[0002] Conveyor belts, as core equipment for material handling in industrial production, are widely used in mining, ports, metallurgy, chemical and other industries. With the escalating global energy crisis and increasingly stringent environmental requirements, the need for energy conservation in long-distance, high-capacity conveyor belts is becoming increasingly urgent. The energy consumption of conveyor belts mainly stems from the rolling friction between the cover rubber and the rollers and idlers; therefore, reducing the rolling resistance of the cover rubber is key to achieving energy conservation in conveyor belts.
[0003] In existing technologies, conveyor belt cover rubber is mostly prepared using a combination of natural rubber and nickel-based butadiene rubber as the base rubber, along with a common sulfur vulcanization system. However, this traditional formulation has significant drawbacks: 1. Nickel-based butadiene rubber has high heat generation and high rolling resistance, resulting in high energy consumption during transportation; 2. Conventional sulfur vulcanization systems are dominated by polysulfide bonds with low bond energy, making them prone to breakage when the rubber is heated, resulting in significant hysteresis loss and further exacerbating rolling resistance. To reduce rolling resistance, some technologies employ efficient vulcanization systems. However, while these systems can reduce rolling resistance, they significantly decrease the tensile strength and abrasion resistance of the cover rubber, shortening its service life.
[0004] Referring to the existing publication number CN112592520B, a low-roller-resistance energy-saving rubber conveyor belt and its cover rubber are described. The conveyor belt cover rubber uses butadiene rubber and natural rubber as raw rubber, and is mixed with clay, and is combined with specific auxiliary materials such as chlorinated paraffin, decabromodiphenyl ether, paraffin oil, and liquid coumarone. The specific material formula and process steps make the finished rubber have a low viscoelastic coefficient, thereby reducing the running resistance of the conveyor roller and the energy consumption of the conveyor.
[0005] Furthermore, existing technologies do not fully utilize the synergistic effects of different base rubbers. A single base rubber or a simple combination of base rubbers cannot simultaneously meet the comprehensive requirements of low rolling resistance, high tensile strength, and good abrasion resistance. For example, while epoxy natural rubber possesses high elasticity and oil resistance, its rolling resistance is poor when used alone; rare earth butadiene rubber, while exhibiting low rolling resistance and abrasion resistance, has room for improvement in elasticity and processing performance. Therefore, developing a conveyor belt cover rubber that achieves both low rolling resistance and excellent physical and mechanical properties through the synergistic effect of base rubbers and optimized formulation systems and process parameters has become a pressing technical problem to be solved in this field. Summary of the Invention
[0006] (a) Technical problems to be solved To address the shortcomings of existing technologies, this invention provides an energy-saving, low-rolling-resistance conveyor belt cover adhesive and its production method, solving the problem that existing conveyor belt cover adhesives cannot simultaneously meet the requirements of low rolling resistance, high tensile strength, good wear resistance, and excellent processing performance, resulting in high energy consumption and short service life for long-distance conveying.
[0007] (II) Technical Solution To achieve the above objectives, the present invention is implemented through the following technical solution: an energy-saving and low rolling resistance conveyor belt cover rubber, the raw materials of which, by weight, include the following components: 55-65 parts epoxy natural rubber, 25-35 parts rare earth butadiene rubber, 8-12 parts high styrene rubber, 35-45 parts high-structure carbon black, 10-20 parts high-dispersion silica, 1.2-1.8 parts silane coupling agent, 3-5 parts softener, 4-6 parts indirect zinc oxide, 1.2-1.8 parts stearic acid, 1.2-1.8 parts antioxidant 4010NA, 1.5-2.1 parts antioxidant RD, and 2.5-5.5 parts vulcanization system; The vulcanization system is an effective vulcanization system, specifically including 1.3-2.7 parts of sulfur, 1.0-1.5 parts of accelerator NOBS and 0.2-0.4 parts of anti-scorching agent CTP. It is mainly composed of monosulfide bonds with high bond energy and is not easy to break, which reduces heat generation and rolling resistance, while ensuring vulcanization stability.
[0008] Preferably, the epoxy natural rubber is ENR-50, and the molecular formula of ENR-50 is: -[(CH2)-C(CH3)(H)-C(O)-(CH2)-], which reacts with performic acid in the C=C atom to generate epoxy group -C(O)-. The functional material obtained by epoxidative modification of natural rubber has an epoxy group content of 45%-55%, which combines the high elasticity of natural rubber and the oil resistance advantage of epoxy group.
[0009] Preferably, the rare earth butadiene rubber is neodymium-based rare earth butadiene rubber with a Mooney viscosity ML(1+4) of 45-60 at 100°C.
[0010] Butadiene rubber: Molecular formula: -[CH2-CH=CH-CH2]-.
[0011] Butadiene rubber is a structurally regular synthetic rubber polymerized from butadiene. Depending on the catalyst, it can be divided into nickel-based, cobalt-based, titanium-based, and rare earth-based (neodymium-based) butadiene rubber. Most butadiene rubber is nickel-based. Compared with nickel-based butadiene rubber, rare earth butadiene rubber has higher elasticity, better tensile properties, lower heat generation and rolling resistance, as well as excellent wear resistance and fatigue resistance.
[0012] Rare earth butadiene rubber and epoxy natural rubber exhibit a synergistic effect in the early stage of crosslinking. The C=C double bonds in rare earth butadiene break and the epoxy groups -C(O)- in epoxy natural rubber crosslink together to form a stable tricyclic epoxy group structure of -CCOC-. Under the action of sulfur crosslinking, some covalent bonds are formed, resulting in a more stable three-dimensional network structure with high bond energy, good elasticity, low internal heat generation after deformation, and low hysteresis loss. This significantly reduces hysteresis loss and rolling resistance.
[0013] High-styrene rubber can adjust the hardness and abrasion resistance of the capping compound. When the amount is controlled at 8-12 parts, it can prevent the rubber from becoming less fluid due to excessive amount, thus preventing defects such as insufficient rubber and obvious marks during production.
[0014] Preferably, the high-structure carbon black is N774 carbon black, with an iodine absorption value of 28-36 mg / g and a DBP absorption value of 100-120 cm³ / 100g.
[0015] Preferably, the highly dispersed silica has a specific surface area of 140-160 m² / g and a DBP absorption value of 200-220 cm³ / 100g.
[0016] Preferably, the silane coupling agent is KH-550 or KH-590, and the softener is paraffin oil or naphthenic oil.
[0017] By compounding high-structure carbon black N774 with highly dispersed silica and combining it with a silane coupling agent to form a reinforcing and filling system, the high-structure carbon black improves tensile strength and abrasion resistance, the highly dispersed silica reduces rolling resistance, and the silane coupling agent promotes the bonding of silica with rubber molecular chains, avoids agglomeration, and optimizes the reinforcing effect.
[0018] Softeners can improve processing fluidity. Indirect zinc oxide and stearic acid work synergistically as vulcanization activators. Antioxidant 4010NA and RD are used together to improve aging resistance.
[0019] This invention also provides a method for producing energy-saving, low rolling resistance conveyor belt cover adhesive, specifically including the following steps: S1. First stage mixing: Start the internal mixer, set the speed to 30-40 r / min, the top bolt pressure to 5.0-6.0 kgf / cm³, and the inlet temperature to ≤90℃. Add epoxy natural rubber to the internal mixer and plasticize at 25-35℃ for 50-70 seconds. Then add rare earth butadiene rubber and high styrene rubber and mix for 50-70 seconds. Next, add high-structure carbon black, high-dispersion silica, indirect zinc oxide and softener and mix for 40-60 seconds. Then add stearic acid, antioxidant 4010NA, antioxidant RD and silane coupling agent and mix for 40-60 seconds. Mix the rubber for 50-70 seconds or when the temperature rises to 115-125℃ and discharge the rubber. Transfer the discharged rubber to the open mill. The open mill roll temperature is ≤70℃, the roll gap is 6-8 mm, and the rubber is spun 3 times. After sheeting, let it stand for 10-14 hours to obtain the first stage compound. S2, Two-stage mixing: Add the first-stage compound to the internal mixer, maintain the speed at 30-40 r / min, the pressure of the top plug at 5.0-6.0 kgf / cm³, add the vulcanization system components, mix for 50-70 seconds or discharge the compound when the temperature rises to 95-105℃ to obtain the second-stage compound. S3. Vulcanization: The two-stage compound rubber is vulcanized at 150℃×25min or 185℃×3min to obtain energy-saving and low rolling resistance conveyor belt cover rubber.
[0020] Preferably, in step S1, the plasticizing temperature of the epoxy natural rubber is 30°C, the plasticizing time is 60 seconds, the mixing time is 60 seconds, the discharge temperature is 120°C, and the rubber compound is left to stand for 12 hours.
[0021] Preferably, the mixing time in step S2 is 60 seconds and the glue discharge temperature is 100°C.
[0022] Preferably, the vulcanization conditions in step S3 are 185℃×3min and the vulcanization pressure is 15-20MPa.
[0023] (III) Beneficial Effects This invention provides an energy-saving, low rolling resistance conveyor belt cover adhesive and its production method. Compared with the prior art, it has the following advantages: (1) The energy-saving and low rolling resistance conveyor belt cover rubber and its production method form a stable tricyclic epoxy group structure by breaking the C=C double bond in rare earth cis-butadiene and cross-linking the epoxy group -C(O)- in epoxy natural rubber. Under the action of sulfur cross-linking, some covalent bonds are formed, forming a more stable three-dimensional network structure with high bond energy, good elasticity, small internal heat generation after deformation, and small hysteresis loss.
[0024] (2) The energy-saving and low rolling resistance conveyor belt cover rubber and its production method adopt an effective vulcanization system, mainly based on monosulfide bonds. Monosulfide bonds are not easy to break, generate little heat, and have excellent low rolling resistance performance.
[0025] (3) The energy-saving and low rolling resistance conveyor belt cover rubber and its production method, through precise control of the formula and processing technology, enable the conveyor belt cover rubber to maintain high strength while significantly reducing rolling resistance. The production process of the present invention is simple, easy to industrialize, and has moderate cost, and has good market application prospects.
[0026] (4) The energy-saving and low rolling resistance conveyor belt cover rubber and production method have good processing performance, good rubber flowability, no defects such as missing rubber or obvious scars in the production process, are suitable for large-scale industrial production, have a long service life, and excellent aging resistance, wear resistance and fatigue resistance.
[0027] (5) The energy-saving and low rolling resistance conveyor belt cover rubber and production method improve tensile strength and wear resistance by using high-structure carbon black, reduce rolling resistance by using highly dispersed silica, and promote the combination of silica and rubber molecular chains by silane coupling agent to avoid agglomeration and optimize the reinforcement effect. Attached Figure Description
[0028] Figure 1 This is a flowchart of the production method of the energy-saving and low rolling resistance conveyor belt cover adhesive of the present invention; Figure 2 This is a bar chart comparing the tensile strength of various embodiments and comparative examples in the performance test of this invention; Figure 3 This is a bar chart comparing the RRF values of various embodiments and comparative examples at 50°C in the performance test of this invention. Detailed Implementation
[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] Please see Figures 1 to 3 The present invention provides five technical solutions: an energy-saving and low rolling resistance conveyor belt cover adhesive and its production method, specifically including the following embodiments: Example 1: An energy-saving, low rolling resistance conveyor belt cover rubber, the raw materials of which, by weight, include the following components: 60 parts epoxy natural rubber, 30 parts rare earth butadiene rubber, 10 parts high styrene rubber, 40 parts high-structure carbon black, 15 parts highly dispersed silica, 1.5 parts silane coupling agent, 4 parts softener, 5 parts indirect zinc oxide, 1.5 parts stearic acid, 1.5 parts antioxidant 4010NA, 1.8 parts antioxidant RD, and 3.5 parts vulcanization system; The vulcanization system is an effective vulcanization system, specifically including 2 parts sulfur, 1.2 parts accelerator NOBS and 0.3 parts anti-scorching agent CTP. It is mainly composed of monosulfide bonds with high bond energy and is not easy to break, which reduces heat generation and rolling resistance, while ensuring vulcanization stability.
[0031] In this embodiment of the invention, the epoxy natural rubber is ENR-50, and the molecular formula of ENR-50 is: -[(CH2)-C(CH3)(H)-C(O)-(CH2)-], which reacts with performic acid in the C=C atom to generate an epoxy group -C(O)-. The functional material obtained by epoxidative modification of natural rubber has an epoxy group content of 50%.
[0032] In this embodiment of the invention, the rare earth cis-butadiene rubber is neodymium-based rare earth cis-butadiene rubber with a Mooney viscosity ML(1+4) of 53 at 100°C.
[0033] In this embodiment of the invention, the high-structure carbon black is N774 carbon black, with an iodine absorption value of 32 mg / g and a DBP absorption value of 110 cm³ / 100g.
[0034] In this embodiment of the invention, the specific surface area of the highly dispersed silica is 150 m² / g, and the DBP absorption value is 210 cm³ / 100g.
[0035] In this embodiment of the invention, the silane coupling agent is KH-550, and the softener is paraffin oil.
[0036] This invention also provides a method for producing energy-saving, low rolling resistance conveyor belt cover adhesive, specifically including the following steps: S1. First stage mixing: Start the internal mixer, set the speed to 35 r / min, and the top plug pressure to 5.5 kgf / cm. 3 The rubber inlet temperature is 85℃. Epoxy natural rubber is added to the internal mixer and plasticized at 30℃ for 60 seconds. Then rare earth cis-butadiene rubber and high styrene rubber are added and mixed for 60 seconds. Then high structure carbon black, high dispersion silica, indirect zinc oxide and softener are added and mixed for 50 seconds. Next, stearic acid, antioxidant 4010NA, antioxidant RD and silane coupling agent are added and mixed for 50 seconds. The rubber is then mixed for 60 seconds or discharged when the temperature rises to 120℃. The discharged rubber is transferred to a two-roll mill with a roller temperature of 65℃ and a roller gap of 7mm. The rubber is rolled 3 times and then sheeted and left to stand for 12 hours to obtain a first-stage compound. S2, Two-stage mixing: Add the first-stage compound to the internal mixer, maintain the speed at 35 r / min and the pressure of the top plug at 5.5 kgf / cm³, add the vulcanization system components, mix for 60 seconds or discharge the compound when the temperature rises to 100℃ to obtain the second-stage compound. S3. Vulcanization: The two-stage compound rubber is vulcanized at 185℃ for 3 minutes with a vulcanization pressure of 17MPa to obtain an energy-saving, low rolling resistance conveyor belt cover rubber.
[0037] Example 2: An energy-saving, low rolling resistance conveyor belt cover rubber, the raw materials of which, by weight, include the following components: 60 parts epoxy natural rubber, 30 parts rare earth butadiene rubber, 8 parts high styrene rubber, 35 parts high-structure carbon black, 10 parts highly dispersed silica, 1.2 parts silane coupling agent, 3 parts softener, 4 parts indirect zinc oxide, 1.2 parts stearic acid, 1.2 parts antioxidant 4010NA, 1.5 parts antioxidant RD, and 2.5 parts vulcanization system; The vulcanization system is an effective vulcanization system, specifically comprising 1.3 parts sulfur, 1 part accelerator NOBS, and 0.2 parts scorching inhibitor CTP.
[0038] In this embodiment of the invention, the epoxy natural rubber is ENR-50, and the molecular formula of ENR-50 is: -[(CH2)-C(CH3)(H)-C(O)-(CH2)-], which reacts with performic acid in the C=C atom to generate an epoxy group -C(O)-. The functional material obtained by epoxidative modification of natural rubber has an epoxy group content of 45%.
[0039] In this embodiment of the invention, the rare earth cis-butadiene rubber is neodymium-based rare earth cis-butadiene rubber with a Mooney viscosity ML(1+4) of 45 at 100°C.
[0040] In this embodiment of the invention, the high-structure carbon black is N774 carbon black, with an iodine absorption value of 28 mg / g and a DBP absorption value of 100 cm³ / 100g.
[0041] In this embodiment of the invention, the specific surface area of the highly dispersed silica is 140 m² / g, and the DBP absorption value is 200 cm³ / 100g.
[0042] In this embodiment of the invention, the silane coupling agent is KH-590, and the softener is naphthenic oil.
[0043] This invention also provides a method for producing energy-saving, low rolling resistance conveyor belt cover adhesive, specifically including the following steps: S1. First stage of compounding: Start the internal mixer, set the speed to 30 r / min, the top jack pressure to 5 kgf / cm³, and the inlet temperature to 75°C. Add epoxy natural rubber to the internal mixer and plasticize at 25°C for 50 seconds. Then add rare earth butadiene rubber and high styrene rubber and mix for 50 seconds. Next, add high-structure carbon black, high-dispersion silica, indirect zinc oxide and softener and mix for 40 seconds. Then add stearic acid, antioxidant 4010NA, antioxidant RD and silane coupling agent and mix for 40 seconds. Mix the rubber for 50 seconds or discharge the rubber when the temperature rises to 115°C. Transfer the discharged rubber to the open mill. The open mill roll temperature is 60°C and the roll gap is 6 mm. The rubber is spun 3 times. After sheeting, it is left to stand for 10 hours to obtain the first stage compound. S2, Two-stage mixing: Add the first-stage compound to the internal mixer, maintain the speed of 30r / min, the pressure of the top plug of 5kgf / cm³, add the vulcanization system components, mix for 50 seconds or discharge the rubber when the temperature rises to 95℃, and obtain the second-stage compound. S3. Vulcanization: The two-stage compound rubber is vulcanized at 150℃ for 25 minutes with a vulcanization pressure of 15MPa to obtain an energy-saving, low rolling resistance conveyor belt cover rubber.
[0044] Example 3: An energy-saving, low rolling resistance conveyor belt cover rubber, the raw materials of which, by weight, include the following components: 60 parts epoxy natural rubber, 30 parts rare earth butadiene rubber, 12 parts high styrene rubber, 45 parts high-structure carbon black, 20 parts highly dispersed silica, 1.8 parts silane coupling agent, 5 parts softener, 6 parts indirect zinc oxide, 1.8 parts stearic acid, 1.8 parts antioxidant 4010NA, 2.1 parts antioxidant RD, and 4.9 parts vulcanization system; The vulcanization system is an effective vulcanization system, specifically comprising 2.7 parts sulfur, 1.5 parts accelerator NOBS, and 0.4 parts anti-scorching agent CTP.
[0045] In this embodiment of the invention, the epoxy natural rubber is ENR-50, and the molecular formula of ENR-50 is: -[(CH2)-C(CH3)(H)-C(O)-(CH2)-], which reacts with performic acid in the C=C atom to generate an epoxy group -C(O)-. The functional material obtained by epoxidative modification of natural rubber has an epoxy group content of 55%.
[0046] In this embodiment of the invention, the rare earth cis-butadiene rubber is neodymium-based rare earth cis-butadiene rubber with a Mooney viscosity ML(1+4) of 60 at 100°C.
[0047] In this embodiment of the invention, the high-structure carbon black is N774 carbon black, with an iodine absorption value of 36 mg / g and a DBP absorption value of 120 cm³ / 100g.
[0048] In this embodiment of the invention, the specific surface area of the highly dispersed silica is 160 m² / g, and the DBP absorption value is 220 cm³ / 100g.
[0049] In this embodiment of the invention, the silane coupling agent is KH-550, and the softener is naphthenic oil.
[0050] This invention also provides a method for producing energy-saving, low rolling resistance conveyor belt cover adhesive, specifically including the following steps: S1. First stage of compounding: Start the internal mixer, set the speed to 40 r / min, the top jack pressure to 6 kgf / cm³, and the inlet temperature to 90℃. Add epoxy natural rubber to the internal mixer and plasticize at 35℃ for 70 seconds. Then add rare earth butadiene rubber and high styrene rubber and mix for 70 seconds. Next, add high-structure carbon black, high-dispersion silica, indirect zinc oxide and softener and mix for 60 seconds. Then add stearic acid, antioxidant 4010NA, antioxidant RD and silane coupling agent and mix for 60 seconds. Mix the rubber for 70 seconds or discharge the rubber when the temperature rises to 125℃. Transfer the discharged rubber to the open mill. The open mill roll temperature is 70℃, the roll gap is 8 mm, and the rubber is spun 3 times. After sheeting, let it stand for 14 hours to obtain the first stage compound. S2, two-stage mixing: Add the first-stage compound to the internal mixer, maintain the speed of 40r / min, the pressure of the top plug 6kgf / cm³, add the vulcanization system components, mix for 70 seconds or discharge the rubber when the temperature rises to 105℃, and obtain the second-stage compound. S3. Vulcanization: The two-stage compound rubber is vulcanized at 185℃ for 3 minutes with a vulcanization pressure of 20MPa to obtain energy-saving and low rolling resistance conveyor belt cover rubber.
[0051] Example 4: The technical solution of this example differs from that of Example 1 in that: an energy-saving and low rolling resistance conveyor belt cover rubber, the raw materials of which, by weight, include the following components: 55 parts epoxy natural rubber, 25 parts neodymium rare earth butadiene rubber, 10 parts nickel butadiene rubber, 10 parts high styrene rubber, 40 parts high-structure carbon black, 15 parts high-dispersion silica, 1.5 parts silane coupling agent, 4 parts softener, 5 parts indirect zinc oxide, 1.5 parts stearic acid, 1.5 parts antioxidant 4010NA, 1.8 parts antioxidant RD, 0.5 parts sulfur, 1.2 parts accelerator NOBS, and 0.3 parts anti-scorching agent CTP.
[0052] Example 5: The technical solution of this example differs from that of Example 1 in that: an energy-saving and low rolling resistance conveyor belt cover rubber, the raw materials of which, by weight, include the following components: 65 parts epoxy natural rubber, 35 parts neodymium rare earth butadiene rubber, 10 parts high styrene rubber, 40 parts high-structure carbon black, 15 parts high-dispersion silica, 1.5 parts silane coupling agent, 4 parts softener, 5 parts indirect zinc oxide, 1.5 parts stearic acid, 1.5 parts antioxidant 4010NA, 1.8 parts antioxidant RD, 0.5 parts sulfur, 1.2 parts accelerator NOBS, and 0.3 parts anti-scorching agent CTP.
[0053] Comparative Example 1: The conveyor belt cover rubber was prepared using nickel-based butadiene rubber instead of neodymium-based rare earth butadiene rubber. An energy-saving, low rolling resistance conveyor belt cover rubber, its raw materials by weight, include the following components: 60 parts epoxy natural rubber, 30 parts nickel-based butadiene rubber, 10 parts high-styrene rubber, 40 parts high-structure carbon black, 15 parts highly dispersed silica, 1.5 parts silane coupling agent, 4 parts softener, 5 parts indirect zinc oxide, 1.5 parts stearic acid, 1.5 parts antioxidant 4010NA, 1.8 parts antioxidant RD, 2 parts sulfur, 1.2 parts accelerator NOBS, and 0.3 parts anti-scorching agent CTP.
[0054] The specific production method of energy-saving and low rolling resistance conveyor belt cover rubber based on Comparative Example 1 is as follows: (1) A stage of mixing: 1. Start the internal mixer, set the speed to 35 r / min, the top jack pressure to 5.5 kgf / cm³, and the inlet temperature to 85℃; 2. Add epoxy natural rubber and masticate at 30°C for 60 seconds; 3. Add nickel-based cis-butadiene rubber and high-styrene rubber, and mix for 60 seconds; 4. Add high-structure carbon black, highly dispersed silica, indirect zinc oxide, and softener, and mix for 50 seconds; 5. Add stearic acid, antioxidant 4010NA, antioxidant RD, and silane coupling agent, and mix for 50 seconds; 6. Mix the glue for 60 seconds, and discharge the glue when the temperature reaches 120℃; 7. The rolling mill has a roller temperature of 65℃ and a roller gap of 7mm. The rubber is spread 3 times, and the sheet thickness is 3mm. After standing for 12 hours, a first-stage compound rubber is obtained.
[0055] (2) Two-stage mixing: 1. Add a section of compounded rubber to the internal mixer, maintain a speed of 35 r / min, and a top jack pressure of 5.5 kgf / cm³; 2. Add accelerator NOBS, anti-scorching agent CTP, and sulfur / sulfur carrier DTDM, mix for 60 seconds, and discharge the rubber when the temperature reaches 100℃ to obtain the two-stage compound.
[0056] (3) Sulfidation: Flat vulcanizing machine vulcanization, vulcanization conditions: 185℃×3min (vulcanization performance test), 150℃×25min (physical properties and rolling resistance test), vulcanization pressure 18MPa.
[0057] Comparative Example 2: The technical solution of this comparative example differs from that of Example 1 in that it increases the amount of high styrene. Specifically, it is an energy-saving and low rolling resistance conveyor belt cover rubber, the raw materials of which, by weight, include the following components: 60 parts of epoxy natural rubber, 30 parts of neodymium rare earth butadiene rubber, 15 parts of high styrene rubber, 40 parts of high-structure carbon black, 15 parts of highly dispersed silica, 1.5 parts of silane coupling agent, 4 parts of softener, 5 parts of indirect zinc oxide, 1.5 parts of stearic acid, 1.5 parts of antioxidant 4010NA, 1.8 parts of antioxidant RD, 2 parts of sulfur, 1.2 parts of accelerator NOBS, and 0.3 parts of anti-scorching agent CTP.
[0058] Comparative Example 3: The technical solution of this comparative example differs from that of Example 1 in that the sulfur in the vulcanization system is replaced with sulfur carrier DTDM. Specifically, it is an energy-saving and low rolling resistance conveyor belt cover rubber, the raw materials of which, by weight, include the following components: 60 parts epoxy natural rubber, 30 parts neodymium rare earth cis-butadiene rubber, 10 parts high styrene rubber, 40 parts high-structure carbon black, 15 parts high-dispersion silica, 1.5 parts silane coupling agent, 4 parts softener, 5 parts indirect zinc oxide, 1.5 parts stearic acid, 1.5 parts antioxidant 4010NA, 1.8 parts antioxidant RD, 1.5 parts sulfur carrier DTDM, 1.2 parts accelerator NOBS, and 0.3 parts anti-scorching agent CTP.
[0059] Performance testing: The following performance tests were conducted on the energy-saving, low rolling resistance conveyor belt cover rubbers of Examples 1-5 (covering the formulation dosage range) and Comparative Examples 1-3 (comparing base rubber type, high styrene dosage, and vulcanization system): Vulcanization performance test: ML, MH, T10, and T90 were tested at 185℃ for 3 min using a vulcanizer; Physical and mechanical property tests: Shore hardness (GB / T 39693.4-2025), tensile strength / elongation (GB / T528-2009), abrasion (GB / T 1689-2014, NBS method); Low rolling resistance performance testing: E′ and tanδ under DMA testing conditions of -50℃ to 50℃, 1.5% strain, and 10Hz, calculated. , where tanδ is the loss factor and E′ is the energy storage modulus (material rigidity).
[0060] The experimental equipment is shown in Table 1.
[0061] Table 1. Experimental Equipment Information
[0062] The results of the vulcanization performance test are shown in Table 2.
[0063] Table 2. Vulcanization performance test results (185℃×3min)
[0064] As shown in Table 2, the T10 (0.37-0.41 min) and T90 (1.55-1.62 min) of Examples 1-5 are reasonable, and the vulcanization process is stable with no risk of scorching. The MH of Comparative Example 1 (nickel-based cis-butadiene) is low, and the crosslinking density is insufficient. The ML / MH of Comparative Example 2 (excess styrene) is too high, and the rubber compound is too hard. The T90 of Comparative Example 3 (sulfur carrier vulcanization) is too long, and the vulcanization efficiency is low.
[0065] The results of the physical and mechanical performance tests are shown in Table 3.
[0066] Table 3. Test results of physical and mechanical properties (150℃×25min)
[0067] As shown in Table 3, Examples 1-5 have tensile strength ≥23.5MPa, elongation ≥525%, and wear ≤82mm³, demonstrating excellent overall performance. Comparative Example 1 (nickel-based cis-butadiene) has slightly poor wear resistance / tensile properties. Comparative Example 2 (high styrene excess) has an elongation of only 485% and insufficient flexibility. Comparative Example 3 (sulfur carrier vulcanization) has low tensile strength and wear resistance.
[0068] The test results for low rolling resistance are shown in Table 4.
[0069] Table 4 Test results of low rolling resistance RRF value
[0070] As shown in Table 4, the RRF values of Examples 1-5 are lower than those of Comparative Examples 1-2 across the entire temperature range. Example 1 has the best energy-saving effect with an RRF of only 0.043 at 50℃. Comparative Example 1 (nickel-based cis-butadiene) has a significantly higher RRF, Comparative Example 2 (excess styrene) has the highest rolling resistance, and Comparative Example 3 (sulfur-supported vulcanization) has a similar RRF but poor physical properties. Figure 2 and Figure 3 It can be seen that Example 1 has the lowest RRF value (0.043) and the highest tensile strength (25.7MPa), achieving a perfect balance between low rolling resistance and high strength.
[0071] In summary, this invention utilizes the synergistic effect of C=C double bond breaking in rare earth butadiene and -C(O)- crosslinking of epoxy groups in epoxy natural rubber to form a stable -CCOC- tricyclic epoxy group structure. Under the action of sulfur crosslinking, some covalent bonds are formed, resulting in a more stable three-dimensional network structure with high bond energy, good elasticity, low internal heat generation after deformation, and low hysteresis loss. By employing an effective vulcanization system dominated by monosulfide bonds, which are not easily broken and generate little heat, the invention achieves excellent low rolling resistance. Through precise control of the formulation and processing technology, the invention further enhances the stability of the rubber. While maintaining high strength, the tape cover rubber significantly reduces rolling resistance. The production process of this invention is simple, easy to industrialize, and has moderate cost, making it a promising candidate for market applications. It has good processing performance, excellent rubber flowability, and no defects such as missing rubber or obvious scars during the production process. It is suitable for large-scale industrial production, has a long service life, and exhibits excellent aging resistance, wear resistance, and fatigue resistance. By using high-structure carbon black to improve tensile strength and wear resistance, highly dispersed silica to reduce rolling resistance, and silane coupling agents to promote the bonding of silica with rubber molecular chains, avoid agglomeration, and optimize the reinforcing effect.
[0072] Furthermore, any content not described in detail in this specification is existing technology known to those skilled in the art.
[0073] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0074] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. An energy-saving, low rolling resistance conveyor belt cover adhesive, characterized in that: The raw materials, by weight, include the following components: 55-65 parts epoxy natural rubber, 25-35 parts rare earth butadiene rubber, 8-12 parts high styrene rubber, 35-45 parts high-structure carbon black, 10-20 parts high-dispersion silica, 1.2-1.8 parts silane coupling agent, 3-5 parts softener, 4-6 parts indirect zinc oxide, 1.2-1.8 parts stearic acid, 1.2-1.8 parts antioxidant 4010NA, 1.5-2.1 parts antioxidant RD, and 2.5-5.5 parts vulcanization system; The vulcanization system is an effective vulcanization system, specifically comprising 1.3-2.7 parts of sulfur, 1.0-1.5 parts of accelerator NOBS, and 0.2-0.4 parts of scorching inhibitor CTP; The epoxy natural rubber is ENR-50, and the molecular formula of ENR-50 is: -[(CH2)-C(CH3)(H)-C(O)-(CH2)-]. It reacts with performic acid in the C=C atom to generate an epoxy group -C(O)-. The functional material obtained by epoxidative modification of natural rubber has an epoxy group content of 45%-55%. The rare earth butadiene rubber is neodymium-based rare earth butadiene rubber with a Mooney viscosity (ML(1+4)) of 45-60 at 100℃. The high-structure carbon black is N774 carbon black with an iodine absorption value of 28-36 mg / g and a DBP absorption value of 100-120 cm⁻¹. 3 / 100g, the specific surface area of the highly dispersed silica is 140-160m² / g, the DBP absorption value is 200-220cm³ / 100g, the silane coupling agent is KH-550 or KH-590, and the softener is paraffin oil or naphthenic oil. Through the synergistic effect of the C=C double bond breaking in rare earth cis-butadiene and the cross-linking of epoxy groups -C(O)- in epoxy natural rubber, a -CCOC- stable tricyclic epoxy group structure is formed. Under the action of sulfur cross-linking, some covalent bonds are formed, forming a more stable three-dimensional network structure. The production method of this energy-saving, low rolling resistance conveyor belt cover rubber specifically includes the following steps: S1. First stage mixing: Start the internal mixer, set the speed to 30-40 r / min, the top bolt pressure to 5.0-6.0 kgf / cm³, and the inlet temperature to ≤90℃. Add epoxy natural rubber to the internal mixer and plasticize at 25-35℃ for 50-70 seconds. Then add rare earth butadiene rubber and high styrene rubber and mix for 50-70 seconds. Next, add high-structure carbon black, high-dispersion silica, indirect zinc oxide and softener and mix for 40-60 seconds. Then add stearic acid, antioxidant 4010NA, antioxidant RD and silane coupling agent and mix for 40-60 seconds. Mix the rubber for 50-70 seconds or when the temperature rises to 115-125℃ and discharge the rubber. Transfer the discharged rubber to the open mill. The open mill roll temperature is ≤70℃, the roll gap is 6-8 mm, and the rubber is spun 3 times. After sheeting, let it stand for 10-14 hours to obtain the first stage compound. S2, Two-stage mixing: Add the first-stage compound to the internal mixer, maintain the speed at 30-40 r / min, the pressure of the top plug at 5.0-6.0 kgf / cm³, add the vulcanization system components, mix for 50-70 seconds or discharge the compound when the temperature rises to 95-105℃ to obtain the second-stage compound. S3. Vulcanization: The two-stage compound rubber is vulcanized at 150℃×25min or 185℃×3min to obtain energy-saving and low rolling resistance conveyor belt cover rubber.
2. The energy-saving, low rolling resistance conveyor belt cover adhesive according to claim 1, characterized in that: In step S1, the plasticizing temperature of the epoxy natural rubber is 30°C, the plasticizing time is 60 seconds, the mixing time is 60 seconds, the discharge temperature is 120°C, and the rubber compound is left to stand for 12 hours.
3. The energy-saving, low rolling resistance conveyor belt cover adhesive according to claim 1, characterized in that: In step S2, the mixing time is 60 seconds and the glue discharge temperature is 100℃.
4. The energy-saving, low rolling resistance conveyor belt cover adhesive according to claim 1, characterized in that: In step S3, the vulcanization conditions are 185℃ for 3 minutes and the vulcanization pressure is 15-20 MPa.
Citation Information
Patent Citations
A low-roller-resistance, energy-saving rubber conveyor belt and its cover rubber
CN112592520B
Ore-separating highly-wear-resistant and anti-corrosive ore pulp conveying pipeline rubber lining material and preparation process
CN104403139A
A rubber material for improving the durability of semi-steel tires and a preparation method thereof
CN119751989A